Characterization of a Novel Tanay Virus Isolated From Anopheles sinensis Mosquitoes in Yunnan, China - Zhao, Lu; Mwaliko, Caroline; Atoni, Evans; Wang, Yujuan; Zhang, Yunzhi; Zhan, Jianbo; Hu, Xiaomin; Xia, Han; Yuan, Zhiming (Frontiers in Microbiology, 2019)
Globally, mosquitoes are known to be competent vectors to various arboviruses that cause serious and debilitating diseases to humans and animals. Conversely, mosquitoes harbor a wide array of insect specific viruses (ISVs) that are generally neglected. Extensive characterization of these ISVs is important in understanding their persistence infection effect on host behavior and arbovirus transmission. Herein, we report first time isolation of Tanay virus (TANAV) isolate YN15_103_01 in Anopheles sinensis mosquitoes from Yunnan Province, China. Phylogenetically, the isolate’s nucleotide identity had more than 14.47% variance compared to previous TANAV isolates, and it clustered into an independent branch within the genus Sandewavirus in the newly proposed taxon Negevirus. TANAV growth and high titers was attained in Aag2 cells (107 PFU/mL) but with no CPE observed up to 7 d.p.i, compared to C6/36 cells that exhibited extensive CPE at 48 h.p.i with titers of 107 PFU/mL. Contrarywise, the viral isolate did not replicate in vertebrate cell lines. Electron microscopy analyses showed that its final maturation process takes place in the cell cytoplasm. Notably, the predicted viral proteins were verified to be corresponding to the obtained SDS-PAGE protein bands. Our findings advance forth new and vital knowledge important in understanding insect specific viruses, especially TANAV.